Cuidados enfermeros postquirúrgicos en paciente con ileostomía por trauma abdominal penetrante - Pisco Macías, Karla Thaís (2024)
The present case study aims to highlight the importance of specific post-surgical nursing care oriented to the recovery of a patient with ileostomy due to penetrating abdominal trauma. The case of a 22 year and 2 month old female patient post emergency exploratory laparotomy surgery with ileostomy as a temporary surgical approach is presented. A nursing care plan based on Marjory Gordon's model is implemented, focused on post-surgical nursing care in a patient with ileostomy due to penetrating abdominal trauma, through comprehensive assessment, prioritization of nursing diagnoses, planning of interventions and evaluation of the results, with the purpose of preventing complications related to temporary ileostomy in the patient. Interview and observation techniques were used, achieving the assessment of the eleven functional health patterns of Marjory Gordon and establishing the nursing care process based on the NANDA Taxonomy, the Nursing Outcomes Classification System (NOC) and the Nursing Interventions Classification System (NIC). The effectiveness of nursing interventions aimed at acute pain management, control of nutritional imbalance, maintenance of tissue integrity, prevention of surgical wound infections is highlighted, achieving the proposed objectives and thus improving the patient's quality of life.